The younger, the better? Speech perception development in adolescent vs. adult L3 learners - Nelson, Christina (Yearbook of the Poznan Linguistic Meeting, 2020)
Whereas the belief “the younger, the better” regarding foreign language learning seems to hold tenaciously, studies comparing learners of different starting ages attest that in instructed (as opposed to naturalistic) learning contexts, a younger age of onset does not automatically yield better results. However, little is known about how multilingual learners from different age groups develop in their non-native languages over time. The present study thus investigates the understudied domain of perceptual development with seven adolescents aged 12–13 and seven adults aged 19–39 (L1 German, L2 English) over the first year of L3 Polish instruction (tested after one, three, five, and ten months). The sound contrast under scrutiny was /v–w/, which only exists in the learners’ L2 and L3. As expected, in the ABX task, adults performed better than adolescents in both languages at most testing times and generally showed a slight upward trend in both their L2 and L3 learning trajectories. For the adolescents, development was more non-linear. Further, a boosting ‘novelty effect’ was found for the younger learner group: After only a few hours of L3 instruction, they perceived the contrast more consistently and faster than in L2 and at any other testing time, performing within the adults’ range.